Numerical Study on Wave-Ice Interaction in the Marginal Ice Zone - Tiecheng Wu; Wanzhen Luo; Dapeng Jiang; Rui Deng; Shuo Huang (Journal of Marine Science and Engineering, 2020)
The effect of waves on ice sheet is critical in the marginal ice zone (MIZ). Waves break large sea ice into small pieces and cause them to collide with each other. Simultaneously, the interaction between sea ice and waves attenuates these waves. In this study, a numerical research is conducted based on a computational fluid dynamics (CFD) method to investigate the response of single ice floe to wave action. The obtained results demonstrate that the sea ice has a violent six degree of freedom (6DoF) motion in waves. Ice floes with different sizes, thicknesses, and shapes exhibit different 6DoF motions under the action of waves. The heave and surge response amplitude operator (RAO) of the sea ice are related to wavelength. Furthermore, the overwash phenomenon can be observed in the simulation. The obtained results are compared with the model test in the towing tank based on artificial ice, and they agree well with test results.

Image-Forming Visual Basis of Empathy for Pain in Mice - Kai-Wen Geng; Rui Du; Na Wei; Chun-Li Li; Yan Wang; Wei Sun; Tao Chen; Dong-Yu Wei; Yang Yu; Ting He; Wen-Jun Luo; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2020)

Correction to: Diffuse leptomeningeal glioneuronal tumor in a Chinese adult: a novel case report and review of literature - Honghao Xu; Fangqing Chen; Haitao Zhu; Lei Luo; Rui Zhang (Acta Neurologica Belgica, 2020)

Hybrid Partition-Based Patrolling Scheme for Maritime Area Patrol with Multiple Cooperative Unmanned Surface Vehicles - Jiajia Xie; Rui Zhou; Jun Luo; Yan Peng; Yuan Liu; Shaorong Xie; Huayan Pu (Journal of Marine Science and Engineering, 2020)
Multi-robot cooperative patrolling systems have been extensively employed in the civilian and military fields, including monitoring forest fires, marine search-and-rescue, and area patrol. Multi-robot area patrol problems refer to the activity that a team of robots works cooperatively and regularly to visit the key targets in the given area for security. Following consideration of the low cost and high safety of unmanned surface vehicles (USV), a team of USVs is organized to perform area patrol in a sophisticated maritime environment. In this paper, we establish a mathematical model considering the characteristics of the cooperative patrol task and the limited conditions of USVs. A hybrid partition-based patrolling scheme is proposed for a multi-USV system to visit targets with different importance levels in a maritime area. Firstly, a centralized area partition algorithm is utilized to partition the patrolling area according to the number of USVs. Secondly, a distributed path planning algorithm is applied to planning the patrolling path for each USV to visit the targets in a maritime environment to minimize the length of the patrolling path for the USV team. Finally, comparative experiments between the proposed scheme and other methods are carried out to validate the performance of the hybrid partition-based patrolling scheme. Simulation results and experimental analysis show the efficiency of the proposed hybrid partition-based patrolling scheme compared to several previous patrolling algorithms.

Multi-AUVs Cooperative Target Search Based on Autonomous Cooperative Search Learning Algorithm - Yuan Liu; Min Wang; Zhou Su; Jun Luo; Shaorong Xie; Yan Peng; Huayan Pu; Jiajia Xie; Rui Zhou (Journal of Marine Science and Engineering, 2020)
As a new type of marine unmanned intelligent equipment, autonomous underwater vehicle (AUV) has been widely used in the field of ocean observation, maritime rescue, mine countermeasures, intelligence reconnaissance, etc. Especially in the underwater search mission, the technical advantages of AUV are particularly obvious. However, limited operational capability and sophisticated mission environments are also difficulties faced by AUV. To make better use of AUV in the search mission, we establish the DMACSS (distributed multi-AUVs collaborative search system) and propose the ACSLA (autonomous collaborative search learning algorithm) integrated into the DMACSS. Compared with the previous system, DMACSS adopts a distributed control structure to improve the system robustness and combines an information fusion mechanism and a time stamp mechanism, making each AUV in the system able to exchange and fuse information during the mission. ACSLA is an adaptive learning algorithm trained by the RL (Reinforcement learning) method with a tailored design of state information, reward function, and training framework, which can give the system optimal search path in real-time according to the environment. We test DMACSS and ACSLA in the simulation test. The test results demonstrate that the DMACSS runs stably, the search accuracy and efficiency of ACSLA outperform other search methods, thus better realizing the cooperation between AUVs, making the DMACSS find the target more accurately and faster.

Characterization of a Cu2+, SDS, alcohol and glucose tolerant GH1 β-glucosidase from Bacillus sp. CGMCC 1.16541 - Yi-Rui Yin; Peng Sang; Feng-Li Yang; Tao Li; Run-Feng Yang; Hong-Yan Liu; Zong-Long Luo; Wen-Jun Li; Li-Quan Yang (Antonie van Leeuwenhoek, 2020)

Design, Characterization, and Application of a pH-Triggered In Situ Gel for Ocular Delivery of Vinpocetine - Qun Ma; Rui Luo; Huimin Zhang; Manman Dai; Luyu Bai; Qingsong Fei; Fang Lei; Ning He (AAPS PharmSciTech, 2020)

An improved FAHP based methodology for groundwater potential zones in Longchuan River basin, Yunnan Province, China - Dayou Luo; Xingping Wen; Haonan Zhang; Junlong Xu; Rui Zhang (Earth Science Informatics, 2020)

Development of SNP markers for the bighead carp (Hypophthalmichthys nobilis) by using transcriptomic sequences - Rui An; Jianjun Fu; Bingjie Jiang; Wenbin Zhu; Lanmei Wang; Mingkun Luo; Zaijie Dong (Conservation Genetics Resources, 2020)

Bioaccumulation and biotransformation of arsenic in Leptolyngbya boryana - Feng Zhu; Min Yang; Zhuan-xi Luo; Rui-lian Yu; Gong-ren Hu; Yu Yan (Environmental Science and Pollution Research, 2020)

Decoding Tropospheric Ozone in Hangzhou, China: from Precursors to Sources - Rui Feng; Kun Luo; Jian-ren Fan (Asia-Pacific Journal of Atmospheric Sciences, 2020)

Comparison of Fraction Unbound Between Liver Homogenate and Hepatocytes at 4°C - Keith Riccardi; Sangwoo Ryu; David Tess; Rui Li; Lina Luo; Nathaniel Johnson; Samantha Jordan; Roshan Patel; Li Di (The AAPS Journal, 2020)

Empathic Contagious Pain and Consolation in Laboratory Rodents: Species and Sex Comparisons - Rui Du; Wen-Jun Luo; Kai-Wen Geng; Chun-Li Li; Yang Yu; Na Wei; Jun Chen (Neuroscience Bulletin, 2020)

Stereo Particle Image Velocimetry Measurements of the Wake Fields Behind A Panamax Bulker Ship Model Under the Ballast Condition - Tiecheng Wu; Wanzhen Luo; Dapeng Jiang; Rui Deng; Yulong Li (Journal of Marine Science and Engineering, 2020)
Particle image velocimetry is applied in this study to measure the wake flow field of a Panamax Bulker ship model under the ballast condition. This investigation revealed that the Froude number is 0.167. The time-averaged velocity, turbulent fluctuations, turbulent kinetic energy (TKE), Reynolds stresses, and vorticity information were measured to perform a comparison with the design condition. The time-averaged velocity contours indicated that the ballast and design conditions have distinct hook-like axial velocity contours; however, they appeared at different positions. The big difference under the ballast condition is that the top of the propeller disk area is near the free surface and a region with strong root mean square velocity fluctuation is formed near the free surface. The TKE, the Reynolds stresses, and the hub cap vortex (Hcv) are all affected by the turbulent velocity fluctuation region under the ballast condition. A strong bilge vortex (Bv) is produced when the water flows through the U-shaped stern for the design and ballast conditions.

Natural HgS nanoparticles in sulfide minerals from the Hetai goldfield - Xiang Liu; Rui Liu; Genwen Chen; Xiaoen Luo; Meiqu Lu (Environmental Chemistry Letters, 2020)

Design of the Key Bearing Layer and Secondary Mining Technology for Previously Mined Areas of Small Coal Mines - Rui Wu; P. H. S. W. Kulatilake; Hao Luo; Kui Zhao (Rock Mechanics and Rock Engineering, 2020)

Temporal variations in riverine hydrochemistry and estimation of the carbon sink produced by coupled carbonate weathering with aquatic photosynthesis on land: an example from the Xijiang River, a large subtropical karst-dominated river in China - Rui Yang; Hailong Sun; Bo Chen; Mingxing Yang; Qingrui Zeng; Cheng Zeng; Jie Huang; Huixian Luo; Danhui Lin (Environmental Science and Pollution Research, 2020)

Diffuse leptomeningeal glioneuronal tumor in a Chinese adult: a novel case report and review of literature - Honghao Xu; Fangqing Chen; Haitao Zhu; Lei Luo; Rui Zhang (Acta Neurologica Belgica, 2020)

Random forest–based classsification and analysis of hemiplegia gait using low-cost depth cameras - Guoliang Luo; Yean Zhu; Rui Wang; Yang Tong; Wei Lu; Haolun Wang (Medical & Biological Engineering & Computing, 2020)

Sol-gel hydrothermal synthesis of nano crystalline silicotitanate and its strontium and cesium adsorption - Rong Wang; Zhenggang Luo; Qiuxia Tan; Rui Wang; Shuyuan Chen; Jiancheng Shu; Mengjun Chen; Zhengxue Xiao (Environmental Science and Pollution Research, 2020)

Stimulation of heterotrophic nitrification and N2O production, inhibition of autotrophic nitrification in soil by adding readily degradable carbon - Ting Lan; Rui Liu; Helen Suter; Ouping Deng; Xuesong Gao; Ling Luo; Shu Yuan; Changquan Wang; Deli Chen (Journal of Soils and Sediments, 2020)

Anfibatide Preserves Blood–Brain Barrier Integrity by Inhibiting TLR4/RhoA/ROCK Pathway After Cerebral Ischemia/Reperfusion Injury in Rat - Peng Gong; Rui Li; Hui-Yu Jia; Zheng Ma; Xiao-Yi Li; Xiang-rong Dai; Sheng-Yong Luo (Journal of Molecular Neuroscience, 2020)